Technologies developed to avoid frost damages caused by late frost during bloom in the fruit growing regions of Siófok and Debrecen - Lakatos, L.; Hadvári, M.; Szél, J.; Gonda, I.; Szabó, Z.; Soltész, M.; Sun, Z.; Zhang, J.; Nyéki, J.; Szukics, J. (International Journal of Horticultural Science, 2016)
The aim of the study was to fi nd out which of the methods used to avoid damages of late frosts would be the most effective for the fruit growing practice. Three technologies have been tested in the regions of Siófok and Debrecen-Pallag. The antifrost irrigation proved to be the most advantageous. For that purpose microjet sprayers are used, which are thrifty and do not need for that purpose large containers. With the aim to secure an even distribution of water, the sprayers are distributed on three levels: above and inside of the crown as well as on the level of trunks. On a large scale, a single microjet above the crown level would be suffi cient. By means of a detailed analysis served to set the optimum intervals between spraying phases: with each 15, 10, 5 and 3 minutes during half a minute. The synchronous presence of water and ice below the freezing point, the released freezing heat plus the water used much above the freezing point (9–10 °C) altogether maintains the temperature above around 0°C near the fl owers or growing fruitlets, meanwhile, the surrounding air cools down to –8 °C. The effectiveness of the generally used anti-frost would be increased substantially by the former application of cooling irrigation, which delays the blooming date. The Frostbuster represents a new technology developed for the same purpose of frost defence. It uses butane burning and produces high (80-90°C) temperature with a strong blast of air. On the protected area sensors have been distributed for measuring temperature and relative humidity. The means of the measurements proved a rise of temperature, which was suffi cient to save the fruit trees until the difference is less than –3–3.5 °C. Our analyses stated that paraffi n candles avert the frost until –4 °C. Its success depends largely on the intensity of air movements. A small wind would be enough to frustrate the effect. The results show clearly the utility of Frostbuster and paraffi n candle combined is approved.